Prevalence of Metabolic Disease in Patients with Chronic Obstructive Pulmonary Disease (COPD) at Universitas Airlangga Hospital, Surabaya, Indonesia - Muhammad Muhajir; Arief Bakhtiar; Satriyo Dwi Suryantoro; Wiwin Is Effendi; Irmi Syafa'ah; Farah Fatma Wati (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Chronic obstructive pulmonary disease (COPD) is a major global health problem and remains one of the three leading causes of death worldwide. In addition to respiratory impairment, COPD is often associated with systemic inflammation that contributes to metabolic disorders such as hypertension, diabetes mellitus (DM), dyslipidemia, and obesity. However, data on the prevalence of these comorbidities in Indonesia remain limited. This study aimed to determine the prevalence of metabolic disorders among COPD patients at Universitas Airlangga Hospital in Surabaya, Indonesia. Methods: This retrospective descriptive study reviewed the medical records of COPD patients with metabolic disorders treated at Universitas Airlangga Hospital, Surabaya, Indonesia, from January to December 2024. Thirty-two patients aged >40 years old with complete data were included. Variables assessed included age, gender, smoking history, the Brinkman Index, Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage, the Modified Medical Research Council (mMRC) Dyspnea Scale, and components of metabolic disorders. Patients with incomplete medical records were excluded. The findings were summarized in tables and figures. Results: All patients were male (100%), with a mean age of 61.7±7.07 years old; the majority were 61-70 years old (56.25%). A history of smoking was present in 84.38% of patients, predominantly with a moderate Brinkman Index. The GOLD stage 2 (40.63%) and mMRC grade 0 (56.25%) were the most common. Metabolic disorders were highly prevalent, including: hypertension (81.26%), obesity (50.0%), dyslipidemia (37.50%), and DM (28.13%). Most patients had multiple overlapping disorders. Conclusion: Metabolic disorders were highly prevalent among COPD patients, with hypertension being the most common. Multiple coexisting metabolic disorders were more frequent than single conditions.